A Strategy Framework About Information: a Study of Integrity For Complex Business Environment Characterized By Uncertainty: Ensuring Information Integrity in a Complex and Uncertain Business Environment (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Thispaper investigates the research issue of Information Integrity for complexbusiness environment characterized by uncertainty. The paper begins with astudy of the Strategy framework for homogeneous business environment with ‘nosurprises,’ which the paper identifies as a ‘closed’ system. This leads to thestudy of an informational view of a complex business environment. The paperargues that complex systems are essentially ‘open’ systems, which, with time,undertake shifts in IS goal, direction and targets (i.e., standards for plansand programs). These shifts, and the uncertainty due to system complexity andother environmental factors identified, infest the IS with hitherto unknownerrors resulting in loss of integrity. This calls for “adaptive learning” as arequirement for the Strategy framework. Accordingly, the paper goes on toconstruct the components of the Strategy framework to ensure InformationIntegrity in a complex business environment. In addition to adaptive learningcapability, it comprises the servo control systems built around the meaningfuluse of pre-estimated targets (standards). This brings about improvements inprocesses,  operations, and inputs bycontrolling them to achieve desired outputs and meeting business systemobjectives. Finally, the paper presents a conceptual view of the systemsrepresentation of the Strategy framework.